Deciphering molecular mechanics in the taste masking ability of Maltodextrin: Developing pediatric formulation of Oseltamivir for viral pandemia. (15th May 2021) - Kalra, Atin; Bhat, Pritesh; Kaur, Indu Pal
Graphical abstract: Highlights: Food grade maltodextrin can be effectively used to mask bitter taste of drugs. Complexes of Ost and Mld more palatable than uncomplexed Ost, thereby enhancing medication adherence. Novel ODMT of Ost are stable, devoid of dosing errors and free of choking hazard in pediatric patients. Abstract: Present research work was aimed at masking the bitter taste of anti- viral drug Oseltamivir phosphate (Ost) by complexing it with pea starch maltodextrin- Kleptose Linecaps® (Mld). The Ost groups involved in triggering the bitter sensation were identified by computationally assessing its interaction with human bitter taste receptor hTAS2R 38. A series of exhaustive molecular dynamics (MD) simulation was run using Schrodinger® suite to understand the type of interaction of Ost with Mld. Experimentally, complexes of Ost with Mld were realized by solution method. The complexes were characterized using differential scanning colorimetry (DSC), fourier transform-infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), hot stage microscopy (HSM), scanning electron microscopy (SEM), proton NMR ( 1 H-NMR) and Carbon-13 nuclear magnetic resonance ( 13 C-NMR). Ost-oral dispersible mini tablets (ODMT) were prepared by direct compression and optimised using mixture designs. Finally, bitter taste perception of Ost-ODMT was evaluated in healthy human volunteers of either sex. Computational assessment, involving interaction of Ost with bitter receptor, predicted the involvement of free amino group of Ost in triggering the bitter response whereas, MD simulation predicted the formation of stable complex between Ost and double helical confirmation of Mld. Different characterization techniques confirmed the findings of MD simulation. Results from the taste assessment in human volunteers revealed a significant reduction in bitter taste of prepared Ost-ODMT